A modular engineering strategy for high‐level production of protopanaxadiol from ethanol by Saccharomyces cerevisiae. Issue 3 (31st December 2018) - Zhao, Fanglong; Bai, Peng; Nan, Weihua; Li, Dashuai; Zhang, Chuanbo; Lu, Chunzhe; Qi, Haishan; Lu, Wenyu
Abstract : Ethanol is a more reduced substrate than sugars. Here, 13 C‐metabolic flux analysis (MFA) revealed that ethanol catabolism could supply sufficient acetyl‐CoA and reducing equivalent for PPD biosynthesis. Then, we described modular engineering strategy to optimize a multigene pathway for protopanaxadiol (PPD) production from ethanol in Saccharomyces cerevisiae . PPD biosynthesis was divided into four modules: mevalonate (MVA) pathway module, triterpene biosynthesis module, sterol biosynthesis module, and acetyl‐CoA formation module. Combinatorially overexpressing every gene in MVA pathway and optimizing metabolic balance in triterpene biosynthesis module led to significantly enhanced PPD production (42.34 mg/L/OD600). In sterol biosynthesis module, fine‐tuning lanosterol synthase gene ( ERG7 ) expression using TetR–TetO gene regulation system enabled further production improvement (51.26 mg/L/OD600). Furthermore, increasing cytoplasmic acetyl‐CoA supply by overexpressing a Salmonella ACS ( acetyl‐CoA synthetase gene ) mutant ACS seL641P improved PPD production to 66.55 mg/L/OD600. In 5 L bioreactor, PPD production of the best‐performing strain WLT‐MVA5 reached 8.09 g/L, which has been the highest titer of plant triterpene produced in yeast. © 2018 American Institute of Chemical Engineers AIChE J, 65: 866–874, 2019